The effectiveness of interventions using relaxation therapy to improve breastfeeding outcomes: a systematic review - Mohd Shukri, Nurul Husna; Wells, Jonathan C. K.; Fewtrell, Mary (Wiley Open Access, 2018)
Maternal psychological state is recognised to influence lactation success, largely by affecting milk ejection. Thus, increased psychological distress can disrupt milk flow and in the long‐term, affect milk synthesis. Conversely, it is possible that milk ejection could be improved by using relaxation therapy during breastfeeding. We performed a systematic review to evaluate the effectiveness of interventions using relaxation therapy to improve breastfeeding outcomes and to assess the consequent impact(s) on infant growth and behaviour. A literature search was performed using the PRISMA guidelines where we included intervention studies (including nonrandomised controlled studies) using relaxation therapy in breastfeeding mothers during the post‐natal period. Out of 147 identified records at the initial search, 5 studies were eligible, of which 3 were randomised controlled trials and 2 were nonrandomised or quasi‐experimental studies. These studies were conducted in Europe, America, and India and included 311 mother–infant pairs, of which 64 infants were full‐term and 247 were premature infants. Relaxation therapy was shown to increase milk yield in mothers of preterm infants in 2 randomised trials, however, the milk sampling protocol for these studies could be questioned. None of the studies investigated the consequent effects on infant outcomes. Overall, limited evidence was found on the effectiveness of relaxation therapy on breast milk composition and infant outcomes. Experimental studies with better standardisation of protocol and robust methodological design are needed to investigate the effectiveness of relaxation therapy on both breastfeeding and infant growth and behavioural outcomes.